Alien ocean : anthropological voyages in microbial seas. - Helmreich, Stefan (University of California Press, 2009)
"Alien Ocean" immerses readers in worlds being newly explored by marine biologists, worlds usually out of sight and reach: the deep sea, the microscopic realm, and oceans beyond national boundaries. Working alongside scientists at sea and in labs in Monterey Bay, Hawai'i, the Woods Hole Oceanographic Institution, and the Sargasso Sea and at undersea volcanoes in the eastern Pacific, Stefan Helmreich charts how revolutions in genomics, bioinformatics, and remote sensing have pressed marine biologists to see the sea as animated by its smallest inhabitants: marine microbes. Thriving in astonishingly extreme conditions, such microbes have become key figures in scientific and public debates about the origin of life, climate change, biotechnology, and even the possibility of life on other worlds -- Présentation de l'éditeur.